Penyajian Pesan Terapi Cancer Fighter - Yuniar Suciati; Hasbiansyah (Bandung Conference Series: Communication Management, 2024)
Abstract. Currently, social media has become something taht cannot be separated from everyday life where social media is used as a medium for communication information, one of which is the dissemination of cancer therapy information. This research aims to dertemine the types of message, message appeal, communication style and motivation of content creator as cancer fighter in sharing his experience fighting cancer on his social media accounts. This research use a constructivist paradigm with qualitative case study research methods, in-deph interview data collection techniques and document studies, using informant namely Shella Selpi Lizah, owner of the account social media Tiktok @Shellasl and Instagram @Shellasl_3 as the main informant. The results of this research (1) Obtained 61 types of persuasive messages, 89 types of informatif messages and 16 of types entertainment messages on instagram and tiktok social media. (2) There were messages with emmotional appeals as well as the arrangement of images and the use of typography as message appeal. (3) There was a communication style passive-aggressive and aggressive. (4) Choosing social media instagram and tiktok because they have fast and wide dissemination of information and can provide material benefits as motivation. Abstrak. Saat ini media sosial menjadi sesuatu yang tidak terlepas dari kehidupan sehari-hari dimana media sosial digunakan sebagai media informasi komunikasi, salah satunya ialah penyebaran informasi terapi kanker. Penelitian ini bertujuan untuk mengetahui jenis pesan, daya tarik pesan, gaya komunikasi dan motivasi content creator as cancer fighter dalam membagikan pengalamannya melawan cancer pada akun media sosialnya. Penelitian ini menggunakan paradigma konstruktivis dengan metode penelitian kualitatif studi kasus, teknik pengumpulan data wawancara mendalam dan studi dokumen, menggunakan informan utama yakni Shella Selpi Lizah pemilik akun media sosial tiktok @Shellasl dan instagram @Shellasl_3 sebagai informan utama. Hasil penelitian ini (1) Didapati 61 jenis pesan persuasif, 89 jenis pesan informatif dan 16 jenis pesan hiburan pada media sosial instagram dan tiktoknya. (2) Terdapat pesan dengan emmotional appeals serta penyusunan gambar menggunakan typografi sebagai daya tarik pesan. (3) Memiliki gaya komunikasi pasif-agresif dan agresif. (4) Pemilihan media sosial instagram dan tiktok karena memiliki persebaran informasi yang cepat dan luas serta dapay memberikan keuntungan materi sebagai motivasi.